PENGARUH BENTUK GERAM DENGAN MEMVARIASIKAN SUDUT POTONG PAHAT TERHADAP KEKASARAN PERMUKAAN MATERIAL S45C DENGAN MENGGUNAKAN MESIN BUBUT GEMINIS - Geril Satrio Ramadhan; Zaldy Kurniawan; Muhammad Haritsah Amrullah (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
Shaft is one of the materials that must have a low surface roughness value from the machining process, especially using the Tornos Geminis S.L semi-automatic lathe. The purpose of this study was to determine the effect of the furious form on the surface roughness of the S45C material. This study used factor variables that are thought to affect the shape and surface roughness of the S45C material, namely, the cutting angle of the chisel with a level (80o, 82o, 84o), feeding depth with a level (0.4 mm, 0.6 mm, 0.8 mm) and Spindle rotation with levels (200 RPM, 280 RPM, 360 RPM). The lowest surface roughness value for the S45C material was obtained from the variation of the chisel cutting angle factor of 80º, infeed depth of 0.4 mm, and spindle rotation of 280 RPM with a surface roughness value of 5.171 . From the lowest value of surface roughness, a tubular growl (short) is produced.